Estimated prevalence and impact of the experience of becoming a victim of exhibitionism and frotteurism in Korea: A general population based study. (14th June 2020) - Choi, Boram; Kim, In; Lee, Gyu Y.; Kim, Sanga; Kim, Seung H.; Lee, Jin G.; Lim, Myung H.
Abstract: Exhibitionism and frotteurism are often considered just nuisance crimes but may cause serious distress to the victims. Previous studies of victim experience have focused on specific groups, such as healthcare professionals or university students. To estimate the prevalence of victimisation by exhibitionism and frotteurism among young general population adults in Korea and to describe the impact of such experiences, trained researchers randomly recruited young adults for face to face interviews at transport hubs and on university campuses. In addition, we posted the questionnaire as a Google survey to a limited number of local websites. Data were analysed descriptively. Of 900 people directly approached, 747 (83%) agreed participation, as did 423 online. These two samples were similar demographically, so combined for analyses. Two hundred and thirty‐five (20%) reported experiencing exhibitionism and 130 (11%) frotteurism. Exposure victims were older (means 23.2:21.1 years) and more likely to be women than frotteur victims. All but two exposure and nine frotteur perpetrators were said to be men. Reporting to police was rare (17 exposure, 2 frotteur); most exposure victims (73%) but under half of frotteur victims told family or friends. All but 15% of each group had bad feelings about the experience, varying by experience type. Ten percent of exposure and 20% of frotteur victims described distress lasting months; more reported enduring behaviour changes, like avoiding subways. Although our sample is unlikely to be wholly representative of the general population, our research examines a broader range of people than previous studies. Most victims of these "nuisance crimes" were distressed by them, and, hitherto less well recognised, at least a fifth of such victims may have long‐term distress. Further research could establish the extent to which support outside the family or friends' group or treatment would be indicated.